Analisis Peran Gaya Kepemimpinan Kepala Madrasah Dalam Membentuk Sumber Daya Manusia Berdaya Saing Global - Assaabiqotul Mardliyah; Muhammad Ridwan Basalamah; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study are: 1) to know and understand the leadership style that will be adopted by a madrasah head or leader, 2) to know and understand the development of human resources to face global competition, 3) to know how important the role of madrasah head leadership style in shaping globally competitive human resources. To find out how the leadership style adopted by the head of the madrasah and the development applied to its human resources, researchers used qualitative research methods. The technique of data collection is through interviews, observation and documentation of the intended research subjects and data analysis used include data reduction, data presentation, and drawing conclusions or verification. So that in this study resulted that in terms of leadership style Mr. Head is a leader with the type of Democratic leadership, leaders who are trustworthy and fair (based on nature), Democratic leaders (based on behavior), and leaders who use the theory of path-goaltheory. Meanwhile, in terms of Human Resources Development, the head unites the focus of Human Resources ability development into skills, so that SKA in development includes skills, knowledge, and attitude. Keywords: Head of Madrasah, Leadership Style, Human Resource Development